2013
DOI: 10.1210/en.2012-1661
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Has Multiple Antiamyloidogenic Effects on Human Neuronal Cells

Abstract: Alzheimer's disease is increased in diabetic patients. A defective insulin activity on the brain has been hypothesized to contribute to the neuronal cell dysregulation leading to AD, but the mechanism is not clear. We analyzed the effect of insulin on several molecular steps of amyloid precursor protein (APP) processing and β-amyloid (Aβ) intracellular accumulation in a panel of human neuronal cells and in human embryonic kidney 293 cells overexpressing APP-695. The data indicate that insulin, via its own rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 51 publications
5
39
1
Order By: Relevance
“…Ghanim and Dandona for their comments (1) on our article (2). Their results showing that insulin infusion leads to decreased expression of amyloid precursor protein (APP) and presenilins in human monocytes (3) are in line with reports in cell culture (4) and support the use of insulin in Alzheimer disease (AD) (5). In triple transgenic (3xTg-AD) mice fed with a high-fat diet for 9 months, we have recently shown that an acute insulin injection decreases cortical soluble Ab40 and Ab42 back to the level of animals fed with a control diet only 5 min after the injection.…”
supporting
confidence: 60%
“…Ghanim and Dandona for their comments (1) on our article (2). Their results showing that insulin infusion leads to decreased expression of amyloid precursor protein (APP) and presenilins in human monocytes (3) are in line with reports in cell culture (4) and support the use of insulin in Alzheimer disease (AD) (5). In triple transgenic (3xTg-AD) mice fed with a high-fat diet for 9 months, we have recently shown that an acute insulin injection decreases cortical soluble Ab40 and Ab42 back to the level of animals fed with a control diet only 5 min after the injection.…”
supporting
confidence: 60%
“…The release of Ab into the extracellular compartment can lead to its degradation by membraneassociated and secreted insulin-degrading enzymes [59] or Ab clearance. Along with increasing Ab secretion into the medium, insulin favors a-secretase activity with increased neurotrophic action, inhibits the translocation of the AbPP intracellular domain into the nucleus, and phosphorylates GSK3b, inhibiting its enzymatic activity for reduced tau pathology [60]. Studies have also shown that insulin inhibits the nuclear activity of the AbPP intracellular domain, reduces the transcription of genes that encode pro-amyloidogenic enzymes such as b-secretase and GSK3b, and increases the transcription of anti-amyloidogenic enzymes such as a-secretase and insulin-degrading enzyme [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Along with increasing Ab secretion into the medium, insulin favors a-secretase activity with increased neurotrophic action, inhibits the translocation of the AbPP intracellular domain into the nucleus, and phosphorylates GSK3b, inhibiting its enzymatic activity for reduced tau pathology [60]. Studies have also shown that insulin inhibits the nuclear activity of the AbPP intracellular domain, reduces the transcription of genes that encode pro-amyloidogenic enzymes such as b-secretase and GSK3b, and increases the transcription of anti-amyloidogenic enzymes such as a-secretase and insulin-degrading enzyme [60,61]. Our results together with those of others suggest that enhancing insulin signaling can relieve insulin resistance, have positive effects on the suppressed cholesterol metabolism of neural cells, and promote Ab release from the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, insulin protects against synapse loss induced by AbOs (51). Insulin further favors nonamyloidogenic processing of the amyloid precursor protein in vitro (97) and reduces tau hyperphosphorylation in a rat model of T2D (98). Exendin-4 was recently found to block AbO-induced impairment in insulin signaling in hippocampal cultured neurons (37).…”
Section: Antidiabetes Agents As Novel Therapeutics In Ad: Unraveling mentioning
confidence: 99%